2014
DOI: 10.1007/s00432-014-1762-8
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional roles of survivin-ΔEx3 and survivin-2B for susceptibility to apoptosis in endometrial carcinomas

Abstract: These findings provided evidence that the balance among expression level of survivin variants may contribute to modulation of cell kinetics in Em Ca cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…[36] In this study, the AIs detected by specific nuclear features in HE-stained sections were positively correlated with TUNEL positivity, in line with our previous data. [37] In agreement with other studies, [20,21] In conclusion, the present study provides evidence that Ps lesions within GBM may serve as a specialized microenvironment by acting as a hypoxic niche, in which the HIF-1/pAkt axis is activated, in response to severe hypoxia and promote CSC features in GBM.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…[36] In this study, the AIs detected by specific nuclear features in HE-stained sections were positively correlated with TUNEL positivity, in line with our previous data. [37] In agreement with other studies, [20,21] In conclusion, the present study provides evidence that Ps lesions within GBM may serve as a specialized microenvironment by acting as a hypoxic niche, in which the HIF-1/pAkt axis is activated, in response to severe hypoxia and promote CSC features in GBM.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…The survivin gene produces three alternatively spliced variants, including full length, delta Ex3 (∆Ex3), and 2B transcripts (Figure 4, [49]), which exhibit differential effects on the apoptotic process [50]. Several studies demonstrated the cytoprotective effects of survivin ΔEx3 variants inhibiting the apoptotic process [51]. In contrast, the presence of the survivin 2B isoforms was reported to confer pro-apoptotic properties on cancer cells [51].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Several studies demonstrated the cytoprotective effects of survivin ΔEx3 variants inhibiting the apoptotic process [51]. In contrast, the presence of the survivin 2B isoforms was reported to confer pro-apoptotic properties on cancer cells [51]. Accordingly, relatively high expressions of full length and survivin ∆Ex3 variants are especially correlated with the active progression or poor prognoses of breast, gastric, thyroid, and pituitary cancers [52].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Sustained overexpression of survivin has been shown to be cancer specific 7 - 9 . In addition, elevated expression of survivin plays a significant role in the inhibition of apoptosis 10 - 13 .These factors suggest that survivin is a potential therapeutic target 14 .…”
Section: Introductionmentioning
confidence: 99%